Accelerating the Transformation of Religious Moderation Villages through Multi-Actor Peace Education Ecosystem - Imam Pribadi; Hadi Pajarianto; Nasriandi; Arman Bin Anuar; Elhadfa Laabed (NAJAHA, 2026)
This study addresses ongoing challenges related to intolerance and social cohesion by examining the implementation of Peace Education within the context of Religious Moderation Villages. This study aims to (1) analyse and formulate strategies to integrate relevant and applicable peace education values in the socio-cultural context of moderate villages; and (2) detect and map the role and effectiveness of the social ecosystem in supporting the values of peace education in the daily lives of the community in a sustainable manner. Using a qualitative approach with a case study design, this study involved 150 FGD participants, with 15 key informants interviewed, consisting of religious leaders, youth, women, teachers, KUA (Religious Affairs Office) instructors, police officers, members of parliament, and village officials. Data were collected through in-depth interviews, Focus Group Discussions, and participant observation, then analysed narratively with triangulation of sources and methods. The findings suggest four strategies to accelerate the transformation of Religious Moderation Villages through Peace Education: (1) strengthening individual peace awareness; (2) strengthening family and community-based moderation values; (3) institutionalising religious and cultural values through inclusive education and village governance; and (4) strengthening cross-actor collaboration (religious leaders, cultural leaders, youth, women's groups, village government, and security/social institutional actors). These four strategies work through layered integration across formal, non-formal, and informal learning spaces and across ecosystem levels (individual, family, community, and institution), so that peaceful values become habitual and institutionally supported. Digitalisation, particularly youth engagement through tolerance narratives on social media, serves as a reinforcing mechanism that expands the reach of peace messages and strengthens cross-group interactions beyond face-to-face meetings. These findings produce a data-driven transformation map for scalable community-based peacebuilding. Peace Education serves as an effective approach in strengthening a culture of tolerance at the community level, although this research is still limited to local contexts and requires quantitative testing for broader validation.